2006
DOI: 10.1111/j.1365-2141.2006.06209.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the anticoagulant effect of a direct thrombin inhibitor and a low molecular weight heparin in an acquired antithrombin deficiency in children with acute lymphoblastic leukaemia treated with l‐asparaginase: an in vitro study

Abstract: SummaryThrombosis occurs in 37% of children with acute lymphoblastic leukaemia (ALL) and is related to an l‐asparaginase‐induced acquired antithrombin (AT) deficiency. The incidence dictates the need for anticoagulant prophylaxis. Direct thrombin inhibitors (DTI) are independent of AT for effect and may thus have advantages in this population. The objective of this study was to determine the interaction of an AT deficiency with the anticoagulant effects of a DTI and a low molecular weight heparin (LMWH). Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The study demonstrated a consistent anticoagulant effect of direct thrombin inhibitors (melagatran) independent of antithrombin level in plasma. Conversely, the anticoagulant effect of LMWH was markedly dependent on antithrombin level [37]. In this context, novel oral anticoagulants such as rivaroxaban or dabigatran, which are direct inhibitors of thrombin or factor Xa, do not require monitoring of antithrombin level and may presumably have a lower risk of failure; however, further studies are warranted to confirm these speculations.…”
Section: Management Of Vte and Rechallenge With L-asparaginasementioning
confidence: 76%
See 2 more Smart Citations
“…The study demonstrated a consistent anticoagulant effect of direct thrombin inhibitors (melagatran) independent of antithrombin level in plasma. Conversely, the anticoagulant effect of LMWH was markedly dependent on antithrombin level [37]. In this context, novel oral anticoagulants such as rivaroxaban or dabigatran, which are direct inhibitors of thrombin or factor Xa, do not require monitoring of antithrombin level and may presumably have a lower risk of failure; however, further studies are warranted to confirm these speculations.…”
Section: Management Of Vte and Rechallenge With L-asparaginasementioning
confidence: 76%
“…Only a fraction of patients were re-exposed to asparaginase; the criteria for continuation versus discontinuation of asparaginase are not provided. anticoagulants are direct inhibitors of thrombin or Xa and are not dependent on antithrombin for their activity [37]. The aforementioned pediatric study demonstrated that the use of enoxaparin and antithrombin was more effective than antithrombin alone in preventive VTE during L-asparaginase therapy [33], which indicates that the new oral anticoagulants may be as effective as or perhaps more effective than LMWH and/ or antithrombin replacement in the prevention of asparaginase-related VTE.…”
Section: Future Perspectivementioning
confidence: 80%
See 1 more Smart Citation
“…Clinical data are again lacking but in vitro experiments using plasma from children with L-Asp-induced AT deficiency have demonstrated a consistent anticoagulant response with direct thrombin inhibitors, independent of AT levels, whereas a profound effect on the action of LMWH related to AT concentration was seen. 68 The new oral direct thrombin inhibitors and anti-Xa anticoagulants are currently being assessed in medical patients for thromboprophylaxis, and if these trials demonstrate efficacy and safety then study in L-Asp-treated patients would be warranted. It is likely that pharmacological thromboprophylaxis will have an increasing role in the management of L-Asp-exposed patients.…”
Section: Thromboprophylaxismentioning
confidence: 99%
“…3,8 Additionally, higher AT III levels can result in more effective low-molecular-weight heparin doses. 10 The formulary AT III product at this institution is Thrombate III (Grifols, Research Triangle Park, NC). According to the manufacturer, AT III doses are calculated by the equation [units required (IU) = (desired AT level % − baseline AT level %) × body weight (kg)/1.4].…”
Section: Introductionmentioning
confidence: 99%